WTP vs.WTA: Christmas Presents and the Endowment Effect - Thomas K. Bauer; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Using data on the valuation of Christmas gifts received by students in different fields at a German university, we investigate whether the endowment effect differs between students of economics and other respondents and whether it varies with the market price of the object under consideration. Our estimation results suggest that economics students have both, a significant lower WTP and WTA, indicating that existing studies on the efficiency loss of holiday gifts and experimental studies on the endowment effect that rely on data from economics students may be biased. The result further indicate that the endowment effect is independent of the market price of the object.
Keywords: D01; D49; D61; 330; Loss aversion; endowment effect; Christmas presents; deadweight loss; Willingness to pay; Bildungsniveau; Geschenk; Verhaltensökonomik; Test; Deutschland